THE ROLE OF ORGANIZATIONAL COMMITMENT IN MODERATING THE INFLUENCE OF PROCEDURAL JUSTICE, DISTRIBUTIVE JUSTICE, INTERACTIONAL JUSTICE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Suhartini Suhartini; Amanto Sulaya (IJAB Indonesian Journal of Accounting and Business, 2019)
This research aims to determine the influence of procedural justice, distributive justice and interactional justice on Organizational Citizenship Behavior (OCB) with organizational commitment as an intervening variable. Respondents in this research were 98 employees of Bank Mandiri Diponegoro Yogyakarta with a work period of more than one year. The data collection method uses a questionnaire, which is measured using a Likert scale. The analytical method uses regression analysis and path analysis. The result of this research indicate that firstly, procedural justice, distributive justice, and interactional justice have a significant influence on organizational commitment, simultaneously. Secondly, procedural justice and distributive justice have a significant influence on OCB, partially. Thirdly, interactional justice does not have a significant influence on OCB partially. Fourthly, procedural justice, distributive justice, and interactional justice have a significant influence on OCB, partially and simultaneously. Fifthly, organizational commitment has a significant influence on OCB. Sixthly, the direct influence (the influence of procedural justice, distributive justice and interactional justice on OCB) is greater than the indirect influence (the influence of procedural justice, distributive justice, and interactional justice on OCB through organizational commitment). The result of this research can be used as a reference for Bank Mandiri in creating and improving OCB. This can be realized by providing fair procedures, improving the benefits system, and increasing interaction between employees for the better.